Special issue on entrepreneurship and crises: business as usual? An introduction and review of the literature. Issue 5 (27th May 2019) - Doern, Rachel; Williams, Nick; Vorley, Tim
ABSTRACT: This article reviews the literature on entrepreneurship and crises, capturing where we have been and where we are now, and begins to discuss where we might go next. It centres around how we have come to understand the relationship between entrepreneurship and crises through the application of certain crisis definitions, concepts, typologies, the crisis event sequence, methodologies and empirical settings. It also examines how crises affect entrepreneurship and how entrepreneurship affects crises. The article then introduces in some detail the five manuscripts selected for the special issue and the contributions they make towards developing our understanding of the relationship between entrepreneurship and crises. It notes the advances, gaps and opportunities that emerge from the literature review and special issue papers, and concludes with a way forward for developing further our understanding in this area.